MENILIK IMPLEMENTASI KEWAJIBAN MORAL NATURAL NEGARA UNTUK MENGAKUI, MENGHORMATI MASYARAKAT ADAT SEBAGAI ENTITAS DASAR DARI TERBENTUKNYA ENTITAS NEGARA - Fransiskus Saverius Nurdin (Law Review, 2019)
AbstractThe state began primarily from the most modest legal society and then evolved into a large and modern entity. These entities are anthropological primordial communities that have a continuity that has been carried on until the history of civilization has disappeared. When a primordial entity becomes a large entity (the State), the state (a large entity) has a morally natural obligation to recognize and respect by issuing legal institutions that do not reduce or do not even distort the primordial entity. This research aims to describe how the state implements its natural moral obligations as a representation of citizens. This research finally provides an answer to the discourse that the state is considered negligent to recognize, respect and fulfill the rights of indigenous peoples. Furthermore, this research is normative legal research (library research) with a statutory approach (statue approach).